Potret Phubbing Generasi Z di Tengah Maraknya Konten Kuliner: Peran Adiksi Media Sosial dan Kontrol Diri - Raissa Aulia Haryadi Putri; Yanti Tayo; Cempaka Putrie Dimala (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study analyzes the role of social media addiction and self-control on phubbing behavior among Generation Z followers of Tiktok culinary content in West Java. This study employed a quantitative survey method with a causal-associative design. The study population consisted of Generation Z individuals who follow culinary content on Tiktok, using purposive sampling to select 386 respondents. Data were collected using the Generic Scale of Phubbing (GSP), the Bergen Social Media Addiction Scale (BSMAS), and the Brief Self-Control Scale (BSCS). Data analysis was performed using multiple linear regression, preceded by assumption tests, namely normality and linearity tests. The results indicate that social media addiction has a positive and significant effect on phubbing behavior (p=0,000), while self-control has a negative and significant effect on phubbing behavior (p=0,000). Simultaneously, social media addiction and self-control have a significant effect on phubbing behavior (p=0,000). The results of the coefficient of determination test indicate that the two independent variables account for 59.4% of the variance in phubbing behavior, while the remaining 40.6% is influenced by other variables outside the scope of this study. These findings suggest that higher levels of social media addiction are associated with higher levels of phubbing behavior, whereas better self-control is associated with lower levels of phubbing behavior. This study underscores the importance of strengthening self-control and managing social media use to minimize phubbing behavior among Generation Z. Future research is recommended to examine additional variables such as fear of missing out, loneliness, emotion regulation, or smartphone addiction that may also contribute to phubbing behave.